Rezolvați in R ecuația
a ) (x - 3) × ( - 1 ) - ( x - 1) × 2 = 5
b ) 4 = ( x - 1 ) × ( - 2 ) - ( x + 2 )
.............
Răspunsuri la întrebare
Răspuns de
1
a) (x - 3)×( - 1 )-( x - 1)×2 = 5
-x+3-(2x-2)=5
-x+3-2x+=5
-3x+3=5
-3x=5-3
-3x=2
b) 4 = ( x - 1 )×( - 2 )-( x + 2 )
4=-2x+2-x-2
4=-3x
Alte întrebări interesante
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă